A Global Perspective on Local Meteoric Water Lines: Meta‐analytic Insight Into Fundamental Controls and Practical Constraints. Issue 8 (19th August 2019) - Putman, Annie L.; Fiorella, Richard P.; Bowen, Gabriel J.; Cai, Zhongyin
Abstract: Local meteoric water lines (LMWLs) represent the site‐specific long‐term covariation of hydrogen and oxygen stable isotope ratios. LMWLs have practical utility as a hydrologic framework and as benchmarks for evaluating hydroclimatic processes in isotope‐enabled climate models. In this manuscript, we characterize the global distribution of LMWLs and compare them to LMWLs from model data. To evaluate the sensitivity of the covariance of stable isotope ratios to data set length, we paired time series rarifaction with Bayesian ellipse estimation. We then applied a threshold of 48 months and estimated LMWLs at 398 sites in 25 Köppen climate classes using orthogonal distance regression. Slopes ranged from 4.8 to 10.9, with an average of 7.64 ± 0.64. Intercepts ranged from −24‰ to 27‰, with an average of 6.85 ± 6.2‰. We identified three processes: (1) subcloud evaporation of rain, (2) atmospheric remoistening by rainfall evaporation, and (3) conditions of snow formation as important controls on slopes and intercepts in arid, humid, and seasonally snowy regions, respectively. We compared observational LMWLs with those from a suite of isotope‐enabled climate models. At arid and snowy sites, model data produced higher slopes and intercepts than observational data. At humid sites, model data exhibited dampened variability in slopes and intercepts relative to observational data. These results indicate potential for improvement in the precipitation and/or isotope parameterizations of raindrop evaporation, advection of reevaporated water, evapotranspiration fractionation, and supersaturation in mixed‐phase clouds. This meta‐analysis demonstrates LMWLs utility for identifying specific hydroclimatic and isotopic processes in observations and models. Key Points: The length of record required to calculate a LMWL should depend on the timescale of the process of interest Nonequilibrium hydroclimatic processes are responsible for some of the spatial variation in LMWL slopes and intercepts Isotope‐enabled climate models could improve precipitation and/or isotope parameterizations of nonequilibrium hydroclimatic processes